Ten Clusters Of Rural Development Articles Using Social Network Analysis - Darto Darto; Savitri Aditiany; Rita Myrna; Riki Satia Muharram (Jurnal Manajemen Pelayanan Publik, 2023)
This article presents an in-depth analysis of Rural Development literature through a Social Network Analysis approach. The purpose of the research is to identify and categorize articles related to Rural Development into ten main clusters, focusing on the patterns of interaction and relationships between them. By applying advanced social network analysis methods, this research details the network structure emerging from this literature, revealing how the articles are interconnected and form groups based on relevant themes or concepts. Additionally, articles that have a central role in the network are also identified, highlighting their significant contribution to the understanding of key aspects of Rural Development. The results showed that the study highlighted gaps that indicate the direction of the future research agenda in rural development, with a focus on inter-regional collaboration in Asia and developing countries. Despite limitations, including limited databases and author subjectivity, this study recommends expanding the sample with broader keywords and databases and benchmarking with other bibliometric analysis tools in the future.